Dynamic mechanical analysis - Menard, Kevin P., 1955-; Menard, Noah P. (CRC Press, Taylor & Francis Group, 2020)
"Dynamic Mechanical Analysis (DMA) is a powerful technique for understanding the viscoelastic properties of materials. It has become a powerful tool for chemists, polymer and material scientists, and engineers. Despite this, it often remains underutilized in the modern laboratory. Because of its high sensitivity to the presence of the glass transition, many users limit it to detecting glass transitions that can't be seen by differential scanning calorimetry (DSC). This book presents a practical and straight-forward approach to understanding how DMA works and what it measures. Starting with the concepts of stress and strain, the text takes the reader through stress-strain, creep, and thermomechanical analysis. DMA is discussed as both the instrument and fixtures as well as the techniques for measuring both thermoplastic and thermosetting behavior. This edition offers expanded chapters on these areas, as well as frequency scanning and other application areas. To help the reader grasp the material, study questions have also been added. Endnotes have been expanded and updated"- Resumé vydavatele